Digital literacy health promotion in stunting prevention efforts for Surabaya Hebat Cadres - Jokhanan Kristiyono; Ni Luh Agustini Purnama; Riesta Ayu Oktarina; Yuni Kurniawaty (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
Surabaya Hebat cadres at the Gununganyar Point Center are facing challenges in digital literacy, which hinders the effective dissemination of stunting prevention information. To address this, this community service program aims to implement Appropriate Technology Digital Literacy to enhance the capacity of cadres in health promotion. The implementation method includes intensive training and operational mentoring. Cadres are trained to evaluate health information, understand digital media ethics, and apply effective communication strategies. The 12 members of the Cadres are also guided in the use of digital tools, such as web applications, infographics, and animated videos, to disseminate relevant information. The program results show an increase in digital literacy among cadres from 60 percent to 85 percent, reflecting success in building digital skills. Cadres are now more confident and effective in educating the community, as measured by increased community participation and wider dissemination of information. Health promotion activities by cadres to the community show a higher frequency of health consultations, which initially were only once a month, increasing to four times a month. The results of this activity also show an increase in community participation in stunting prevention initiatives, with the number of residents in the Sentra Point housing area participating rising by 25 percent.